2023
DOI: 10.3390/ani13111824
|View full text |Cite
|
Sign up to set email alerts
|

LSR-YOLO: A High-Precision, Lightweight Model for Sheep Face Recognition on the Mobile End

Abstract: The accurate identification of sheep is crucial for breeding, behavioral research, food quality tracking, and disease prevention on modern farms. As a result of the time-consuming, expensive, and unreliable problems of traditional sheep-identification methods, relevant studies have built sheep face recognition models to recognize sheep through facial images. However, the existing sheep face recognition models face problems such as high computational costs, large model sizes, and weak practicality. In response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Xie et al [39] introduced SE attention in YOLOv5 to improve big mammal species detection from a UAV viewpoint. Zhang et al [43] introduced a coordinated attention (CA) module in YOLOv5s to suppress non-critical information on the face of sheep to recognize the identity of sheep in real time. Given the different lighting conditions and backgrounds present in camera trap images, to better extract wildlife features, we compared the performance of the model after adding different attention modules and found that the addition of the SE attention mechanism can further improve wildlife recognition by 0.09%.…”
Section: Discussionmentioning
confidence: 99%
“…Xie et al [39] introduced SE attention in YOLOv5 to improve big mammal species detection from a UAV viewpoint. Zhang et al [43] introduced a coordinated attention (CA) module in YOLOv5s to suppress non-critical information on the face of sheep to recognize the identity of sheep in real time. Given the different lighting conditions and backgrounds present in camera trap images, to better extract wildlife features, we compared the performance of the model after adding different attention modules and found that the addition of the SE attention mechanism can further improve wildlife recognition by 0.09%.…”
Section: Discussionmentioning
confidence: 99%
“…The YOLO framework effectively distinguishes target and background areas to achieve target recognition [30,31] . The YOLOv5s is composed of inputs, backbone, neck, head, and output.…”
Section: Coated Red Clover Seed Recognition Model 231 Yolov5smentioning
confidence: 99%
“…To evaluate the performance of the proposed model more fairly and accurately, this paper used precision (P), recall (R), F1-Score(F1), and AP for the performance evaluation and comparison [30]. The formulae for each metric used in this paper are presented below:…”
Section: Experimental Evaluation Metricsmentioning
confidence: 99%